2002
DOI: 10.1038/sj.gene.6363861
|View full text |Cite
|
Sign up to set email alerts
|

RAGE and arthritis: the G82S polymorphism amplifies the inflammatory response

Abstract: The receptor for advanced glycation end products (RAGE)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

17
312
3
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 348 publications
(333 citation statements)
references
References 54 publications
17
312
3
1
Order By: Relevance
“…In the same study Hofman et al 4 reported that the genetic variant that correlates with the expression of the more active RAGE 82S receptor, confers increased susceptibility for the development of RA. However, the picture is more complicated as it seems due to the high degree of linkage disequilibrium within the MHC.…”
mentioning
confidence: 93%
See 4 more Smart Citations
“…In the same study Hofman et al 4 reported that the genetic variant that correlates with the expression of the more active RAGE 82S receptor, confers increased susceptibility for the development of RA. However, the picture is more complicated as it seems due to the high degree of linkage disequilibrium within the MHC.…”
mentioning
confidence: 93%
“…For those reasons it is specially noteworthy that in the same paper Hofmann et al 4 elegantly provide evidence for a functional difference between the naturally occuring RAGE protein variants, ie, the wild-type with a glycine at position 82 and the variant with a serine in that position. The studies revealed significant differences in (i) the Kd between RAGE 82G (Kdෂ122+/−31 nM) and RAGE 82S (Kdෂ77+/−21 nM) receptors, (ii) the EN-RAGE induced phosphorylation of MEK1/2 and p44/42 MAP kinases and NF-B induction (RAGE 82SϾG), and (iii) EN-RAGE induced production of the pro-inflammatory cytokines TNF-␣ and IL-6, and the metalloproteinases (MMP) 3, 9 and 13 (RAGE 82SϾG).…”
mentioning
confidence: 99%
See 3 more Smart Citations